Edukasi Enam langkah Mencuci Tangan di Sekolah Dasar Negeri Kamasan 2 Kabupaten Serang Banten - Firda Asma'ul Husna; Mutria Maharani; Miftahul Fauzan; Khaerunissa All Husna; Alika Nadina Nurazizah; Dhini Herliani; Daniya Putri Kurniawan; Dewi Ardianti; Abigail Cecilia Sihombing; Muhammad Fajar Mubarok; Muhammad Syafiqi Noor Rohmansyah; I'tollah I'tollah; Olga Handika; Ukroma Haekal; Siti Aisyah Rohamdhoni; Neisha Shaquila Nabila Kamil; Uswatun Hasanah; Ayesha Zivanka Anfasyah; Nabila Adawiyah; Alma Tsabitha Sasikirana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Hand washing is a major pillar in clean and healthy living behaviors (PHBS). However, there are still children who do not understand the correct handwashing technique so that germ cleaning is not optimal. This community service activity aims to improve students' knowledge and motor skills in practicing the six steps of hand washing according to World Health Organization (WHO) standards. The method used in this activity is interactive counseling combined with live demonstrations. The stages of the activity include providing material through audiovisual media (video/poster), direct demonstrations by instructors, and independent practice by all participants. In addition, a question and answer session was held to ensure student understanding and corrective feedback on inappropriate movements. Evaluation instruments in the form of observation sheets were used to assess the accuracy of the sequence, duration, and coverage of the hand area when washing. The result of this activity was the success of all participants in practicing the six-step sequence of handwashing correctly independently. The involvement of teachers and school health workers also strengthens the sustainability of this practice through regular monitoring. Through this education, it is hoped that early awareness will arise which has become a routine habit to reduce the risk of disease transmission in the school and home environment and support the creation of a culture of clean living from an early age.